UTILISATION OF BIG DATA ANALYTICS IN ACCOUNTING INFORMATION SYSTEMS TO IMPROVE THE QUALITY OF CORPORATE FINANCIAL DECISION MAKING - Teguh Prakoso; Rina Apriliani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The utilisation of Big Data Analytics (BDA) in accounting information systems provides significant transformation opportunities in the company's financial decision-making process. This study aims to analyse the role of BDA in improving the quality of financial decisions through a literature study approach that reviews various research results and recent scientific publications. The results show that BDA integration enables real-time financial data processing, anomaly detection, trend prediction, and more accurate and comprehensive multidimensional analysis. BDA also contributes to improved audit efficiency, risk management, and integration of financial data with external data to support evidence-based strategic decisions. However, challenges such as the need for large technological infrastructure, data security, human resource competence, and implementation costs are still obstacles that need to be overcome. With the right management strategy, BDA can be an important tool in supporting the transformation of modern accounting functions and strengthening the competitiveness of companies in the digital era.